Simultaneous Quantification of 22 Glucosinolates in 12 Brassicaceae Vegetables by Hydrophilic Interaction Chromatography-Tandem Mass Spectrometry - Liang, X. (American Chemical Society, 2022)
10.1021/acsomega.8b01668